Study on Fracture Mode of Gypsum under Shear Box Loading. Issue 6 (October 2021) - He, Qiang; Liu, Huai-Zhong; Xie, Hong-Qiang; Xiao, Ming-Li; Li, Zhuo
Abstract: The fracture mode under compressive shear loading is the research focus of rock fracture mechanics. In this paper, rock-like material with cracks was used to investigate its fracture mode. The physical and mechanical parameters of gypsum with specific paste-to-water ratio and curing time were measured by uniaxial compression test, and then, the shear box tests with loading angles of 0°, 15°, 30°, 45°, 60°, and 70° were carried out on gypsum specimens with initial double edge cut cracks. Finally, the strain field was monitored by the DIC method to analyze and summarize the phenomenon of crack initiation and propagation, and to analyze the fracture mode under shear box loading. The results show that the failure process of gypsum under uniaxial loading is a tensile split failure, and the fracture propagates through the entire specimen. Under the shear box loading, when the loading angle is less than 30°, the crack propagation presents a splitting tensile failure mode, that is, the crack propagation belongs to Mode I. When the loading angle is greater than 60°, the crack propagation shows shear failure mode after loading, that is, the crack propagation belongs to Mode II. While, when the loading angle is 45°, both the above two conditions exist, and the specimen presents both wing crack and secondary crack, in other words, the failure mode of the specimen is a superposition of shear fracture and tensile fracture. The research results can improve the understanding of the crack propagation mechanism of rock-like materials.